Optimal Power Flow with Hybrid Distributed Generators and Unified Controller - Lakshmi Ravi; Vaidyanathan R Vaidyanathan R; Shishir Kumar D; Prathika Appaiah; S.G. Bharathi Dasan (Universitas Ahmad Dahlan, 2012)
Optimal power flow (OPF) study is conducted on a power system to achieve one of the following objectives: cost/loss minimization or available transfer capability (ATC) calculation in a deregulated environment. Distributed generation (DG) is a small source of electric power conversion from non-conventional energy sources and Hybrid DGs which often the most cost-effective and reliable way to produce power. The optimality of control variables and minimum value of objective functions in OPF study would definitely change when DGs are interconnected to the grid. The change would be respect to the location, quantity and combination of power injection by DGs. On the other hand, FACTS controllers are effective in utilizing the existing of transmission network which is very important especially in a deregulated system. Unified power flow controller (UPFC), a second generation FACTS controller, is well known for minimizing the cost of generation/losses with a good voltage profile as well as for ATC improvement. This paper conducts a detailed OPF study on a 9 bus system for the above mentioned three objectives to analyze the effect of DGs with and without UPFC. From the results, it is found that hybrid DGs along with UPFC yields better performance in many aspects.